2006
DOI: 10.1111/j.1365-2354.2006.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical outcomes and prognostic factors of neoadjuvant chemoradiotherapy combined with surgery: intraperitoneal versus extraperitoneal rectal cancer

Abstract: Neoadjuvant chemoradiotherapy (CRT) is a widely purposed and performed treatment for rectal cancer. Downstaging effects possibly enhance the rate of curative surgery and may enable sphincter preservation in low-lying tumours. The current study examines the clinical outcomes in patients enrolled in a neoadjuvant CRT-surgery protocol for rectal cancer, distinguishing between intraperitoneal and extraperitoneal cancer. From 1994 to 2003, 58 patients with a primary diagnosis of rectal cancer were enrolled in a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Different tumor biologies, the technical difficulties of the surgical procedures, and the administration of adjuvant treatment in extraperitoneal rectal cancer [9,10,18,19] suggest the need for studies that focus on the CRM statuses of patients with 'wholly' extraperitoneal rectal cancer. From a technical and anatomical perspective, it is more difficult to achieve a clear CRM for extraperitoneal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Different tumor biologies, the technical difficulties of the surgical procedures, and the administration of adjuvant treatment in extraperitoneal rectal cancer [9,10,18,19] suggest the need for studies that focus on the CRM statuses of patients with 'wholly' extraperitoneal rectal cancer. From a technical and anatomical perspective, it is more difficult to achieve a clear CRM for extraperitoneal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The peritoneal reflection is a landmark used for evaluating the rectum anteriorly, and divides the rectum into two parts, that is, the intraperitoneal and extraperitoneal regions, which are referred to considerations of the venous and lymphatic drainage systems of the rectum 2. In particular, extraperitoneal rectal tumours disseminate mainly through the systemic pelvic venous and lateral lymphatic drainage systems, whereas intraperitoneal rectal tumours disseminate mainly through the superior haemorrhoidal and inferior mesenteric venous and lymphatic drainage systems 2.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, extraperitoneal rectal tumours disseminate mainly through the systemic pelvic venous and lateral lymphatic drainage systems, whereas intraperitoneal rectal tumours disseminate mainly through the superior haemorrhoidal and inferior mesenteric venous and lymphatic drainage systems 2. Furthermore, Benzoni et al concluded that tumour location in relation to the peritoneal reflection is a prognostic factor in rectal cancer 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The DFS and OS were poor for extraperitoneal than for intraperitoneal rectal cancer. Data from Genovesi et all confirmed these evaluations in the multivariate analysis, with a negative influence of extraperitoneal tumor location on DFS and CSS.…”
Section: -14mentioning
confidence: 96%